WebSphere V5 for Linux on zSeries connectivity handbook - Anavi-Chaput, Viviane (IBM redbooks., 2004)
This IBM Redbooks publication discusses Linux-based Java applications connecting to z/OS and VSE backend environments on zSeries. This book describes the implementation and deployment of Websphere Application Server, Java frontend applications, and the J2EE connectors needed on Linux for zSeries to connect to backend applications, such as CICS, IMS, DB2 and MQ on zSeries. This book explains the J2EE Connector architecture and provides the following comprehensive connector scenarios for connections to both z/OS and VSE backend environments: - CICS Transaction Gateway - IMS Connect - WebSphere MQ - JDBC to DB2 - SOAP to CICS.